The Possibilities of Violence and the Skills to Avoid It: On Warfare and Its Absence in Traditional Micronesia - Petersen, Glenn (Anthropologica, 2014)
This article explores some of the ways in which traditional Micronesian societies used the threat of warfare as an impetus to non-violence or, in other words, as a deterrent. Typically, Micronesians spent a good deal of time preparing for battle; war loomed large in their mytho-history and valour was a key cultural value. But these societies in fact depended heavily upon their dispersed matriclans for a range of alternative options to actual combat. Drawing upon this material, I argue that societies are not necessarily either peaceful or violent and that the appearance of bellicosity can mask deep commitments to avoiding open conflict.